2022
DOI: 10.1098/rstb.2021.0441
|View full text |Cite
|
Sign up to set email alerts
|

Thriving together: the benefits of women's social ties for physical, psychological and relationship health

Abstract: The relationship between social support and well-being is well established in social psychology, with evidence suggesting that these benefits are especially prominent among women. When faced with an environmental stressor, women are more likely to adopt a tend-and-befriend strategy rather than fight-or-flight. Furthermore, female friendships tend to be higher in self-disclosure and more frequently relied on for social support, which is associated with physical and psychological benefits. Women are also more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 100 publications
1
8
0
Order By: Relevance
“…In support, several studies characterize women and girls as forming fewer same-sex friendships, investing more in each relationship, being more likely to terminate relationships over social transgressions and being less cooperative than men and boys in same-sex interactions [ 43 , 45 , 53 , 55 61 , 63 66 ]. On the other hand, research from social and health psychology indicates that women are more likely to respond to stressful scenarios by seeking and providing support and engaging in other-oriented strategies despite interacting with strangers, whereas men are more likely to respond selfishly and competitively ([ 69 72 ], reviewed in [ 73 ]). Further, a review on children's prosocial behaviour found that girls were often found to have smaller playgroups, but they were more prosocial than boys in most other respects [ 64 ].…”
Section: Key Themes and Findings From This Issuementioning
confidence: 99%
See 2 more Smart Citations
“…In support, several studies characterize women and girls as forming fewer same-sex friendships, investing more in each relationship, being more likely to terminate relationships over social transgressions and being less cooperative than men and boys in same-sex interactions [ 43 , 45 , 53 , 55 61 , 63 66 ]. On the other hand, research from social and health psychology indicates that women are more likely to respond to stressful scenarios by seeking and providing support and engaging in other-oriented strategies despite interacting with strangers, whereas men are more likely to respond selfishly and competitively ([ 69 72 ], reviewed in [ 73 ]). Further, a review on children's prosocial behaviour found that girls were often found to have smaller playgroups, but they were more prosocial than boys in most other respects [ 64 ].…”
Section: Key Themes and Findings From This Issuementioning
confidence: 99%
“…Kramer ([ 112 ], in this issue) argues that women's cooperation is responsive to a variety of factors, including cultural norms, life-history stage, subsistence strategy and household demography. In a similar vein, research in experimental settings indicates that women's cooperative behaviour may be more sensitive to their social partners' needs and behaviour than men's, and women may be more likely to shift social strategies depending on the costs and benefits of each scenario compared to men ([ 73 , 82 , 113 ], all in this issue).…”
Section: Key Themes and Findings From This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The Social Convoy Model provides a conceptual framework that social support provided by parents in early childhood yields a "secure base" and a "safe haven" when faced with stress in subsequent life (77). These suggested that social support exerts a positive effect on life stress, and this bene t is also prominent in female people (32). The mechanisms by which social support impacts health and well-being are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with males, females were more sensitive to low social support (30) and tended to seek and obtain social support when faced with environmental stressors (31). Therefore, females with BD may bene t more from social support interventions (32). Also, some studies have found that social support was associated with mood symptoms and could buffer the negative impact of childhood trauma on mood symptoms (33,34).…”
Section: Introductionmentioning
confidence: 99%